Anti-Hyperglycemic Effect of Combination Etanolic Extract of Sambiloto (Andrographis paniculata) and Bitter Melon Fruit (Momordica charantia L) on Alloxan-Induced Wistar White Rats - Suswidiantoro, Vicko; Pratiwi, Mida; Safutri, Wina; Satriawan, Ahmad Bayu; Sari, Yuhana (Jurnal Kesehatan, 2023)
Diabetes Mellitus is a metabolic disorder characterized by hyperglycemia caused by a decrease in insulin secretion. Sambiloto leaves (Andrographis paniculata (Burm.f.) Wall. Ex Ness) and bitter melon (Momordica charantia L) are types of plants that are used as regulators of blood sugar levels. The study aimed to determine the effectiveness and effective comparative doses in the combination of sambiloto leaf extract (Andrographis paniculata (Burm.f.) Wall. Ex Ness) and bitter melon (Momordica charantia L) on alloxan-induced Wistar white rats. This study is experimental research with a pre and post-control group design, using a sample of 24 subjects. The data analysis in this study employed normality and homogeneity tests, obtaining a significance result of p>0.05. The development of the ANOVA test revealed a significant value of p